1976
DOI: 10.1111/j.1600-0528.1976.tb00973.x
|View full text |Cite
|
Sign up to set email alerts
|

A survey of traumatized primary anterior teeth in Jerusalem preschool children

Abstract: The prevalence of traumatized primary anterior teeth was studied in 965 5-year-olds attending compulsory kindergartens in West Jerusalem in 1971. The prevalence of children with traumatized teeth was 11.1%. No difference between males and females was found. In most cases only one tooth was affected. The tooth most frequently affected was the maxillary central incisor. The most common type of fracture was that of enamel with or without dentin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
46
2
19

Year Published

1982
1982
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(79 citation statements)
references
References 2 publications
12
46
2
19
Order By: Relevance
“…Again, we observed that the upper central incisors were most often affected by TDIs like other studies [35, 48, 49], and the most common type of TDI is fracture involving the enamel only like others [2, 50]. The upper anterior teeth are more often involved in TDI when compared to the lower anterior teeth because the upper jaw is fixed to the skull making it rigid and increasing the impact of forces directed at the face more on the upper anterior teeth [51].…”
Section: Discussionsupporting
confidence: 78%
“…Again, we observed that the upper central incisors were most often affected by TDIs like other studies [35, 48, 49], and the most common type of TDI is fracture involving the enamel only like others [2, 50]. The upper anterior teeth are more often involved in TDI when compared to the lower anterior teeth because the upper jaw is fixed to the skull making it rigid and increasing the impact of forces directed at the face more on the upper anterior teeth [51].…”
Section: Discussionsupporting
confidence: 78%
“…O desconhecimento por parte dos pais e responsáveis de episódios de trauma é um fato discutido com freqüência na literatura. Estudos demonstram que apenas 50% dos responsáveis por crianças com sinais clínicos de injúrias traumáticas relatam conhecimento sobre história anterior de trauma 8,[13][14][15][16] . Nossos resultados corroboram estes dados e parecem indicar que as injúrias traumáticas na dentição decídua são, muitas vezes, subestimadas ou não percebidas pelos pais e responsáveis.…”
Section: Discussionunclassified
“…The different classification criteria found in the literature makes it difficult to compare the outcomes of different studies. Even so, crown fractures, either complex or not, involving enamel or enamel/dentin, are the most commonly reported types of dentoalveolar traumatic injury [10][11][12]15,[24][25][26][27] . However, da Silva et al 6 found avulsion and luxation as the most prevalent dentoalveolar traumas.…”
Section: Discussionmentioning
confidence: 99%